PENGEMBANGAN INSTRUMEN ASESMEN BERBASIS KURIKULUM MERDEKA DENGAN BERBANTUAN LIVEWORKSHEET PADA MATA PELAJARAN DASAR-DASAR AKUNTANSI - Ivierifanny Berthania Az-Zahra; Rochmawati Rochmawati (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The learning process cannot be separated from learning evaluation, one of which is through assessment. This research aims to develop an merdeka curriculum assessment instrument with the help of Liveworksheets in basics accounting subject, determine the level of suitability of Liveworksheets as a learning assessment and students' responses to Liveworksheet assisted assessments. The development of this assessment uses the ADDIE development model which consists of analysis, design, development, implementation and evaluation. In this research was carried out with test subjects of 20 students from class X accounting at SMK PGRI 2 Sidoarjo. The research instruments used were review sheets and validation from assessment experts, material experts, linguists and graphic experts, analysis of question items using Anates, as well as student response questionnaires. The results of validation from assessment experts were 96%